The Link between Type 2 Diabetes and Neurodegeneration: Roles for Amyloid-ß, Amylin, and Tau Proteins - Bharadwaj, Prashant; Wijesekara, N.; Liyanapathirana, M.; Newsholme, Philip; Ittner, L.; Fraser, P.; Verdile, G. (IOS Press, 2017)
© 2017-IOS Press and the authors. All rights reserved. A wealth of evidence indicates a strong link between type 2 diabetes (T2D) and neurodegenerative diseases such as Alzheimer's disease (AD). Although the precise mechanism remains unclear, T2D can exacerbate neurodegenerative processes. Brain atrophy, reduced cerebral glucose metabolism, and central nervous system insulin resistance are features of both AD and T2D. The T2D phenotype (glucose dyshomeostasis, insulin resistance, impaired insulin signaling) also promotes AD pathology, namely accumulation of amyloid-ß (Aß) and hyperphosphorylated tau and can induce other aspects of neuronal degeneration including inflammatory and oxidative processes. Aß and hyperphosphorylated tau may also have roles in pancreatic ß-cell dysfunction and in reducing insulin sensitivity and glucose uptake by peripheral tissues such as liver, skeletal muscle, and adipose tissue. This suggests a role for these AD-related proteins in promoting T2D. The accumulation of the islet amyloid polypeptide (IAPP, or amylin) within islet ß-cells is a major pathological feature of the pancreas in patients with chronic T2D. Co-secreted with insulin, amylin accumulates over time and contributes to ß-cell toxicity, ultimately leading to reduced insulin secretion and onset of overt (insulin dependent) diabetes. Recent evidence also suggests that this protein accumulates in the brain of AD patients and may interact with Aß to exacerbate the neurodegenerative process. In this review, we highlight evidence indicating T2D in promoting Aß and tau mediated neurodegeneration and the potential contributions of Aß and tau in promoting a diabetic phenotype that could further exacerbate neurodegeneration. We also discuss underlying mechanisms by which amylin can contribute to the neurodegenerative processes.